2016
DOI: 10.1007/s10096-016-2798-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a predictive model for identifying febrile young infants with altered urinalysis at low risk of invasive bacterial infection

Abstract: In 2015, a predictive model for invasive bacterial infection (IBI) in febrile young infants with altered urine dipstick was published. The aim of this study was to externally validate a previously published set of low risk criteria for invasive bacterial infection in febrile young infants with altered urine dipstick. Retrospective multicenter study including nine Spanish hospitals. Febrile infants ≤90 days old with altered urinalysis (presence of leukocyturia and/or nitrituria) were included. According to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
1
13
0
3
Order By: Relevance
“…Although a small number of studies have demonstrated worse outcomes for younger infants with IBI, most have focused solely on mortality, and age cutoffs defining younger infants differed. (2832) Some studies on IBI in young infants have excluded premature infants altogether;(33, 34) and very few have reported outcomes data in relation to prematurity. (18) Age-stratified outcomes data for infants with IBI, particularly febrile infants, has been identified as a research priority.…”
Section: Discussionmentioning
confidence: 99%
“…Although a small number of studies have demonstrated worse outcomes for younger infants with IBI, most have focused solely on mortality, and age cutoffs defining younger infants differed. (2832) Some studies on IBI in young infants have excluded premature infants altogether;(33, 34) and very few have reported outcomes data in relation to prematurity. (18) Age-stratified outcomes data for infants with IBI, particularly febrile infants, has been identified as a research priority.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 However, when they evaluated the performance of the urine dipstick, these models did not assess the performance of leucocyte esterase and the nitrite test separately. The presence of a positive result for nitrite and leucocyte esterase on urinalysis has been proven to be an independent risk factor for bacteraemia in young febrile infants, [8][9][10] but little is known about the specific value of the nitrite test. One study showed that a model that included the urinary nitrite test may be useful for predicting bacteraemia among adult patients with pyelonephritis.…”
mentioning
confidence: 99%
“…La ITU es la infección bacteriana potencialmente grave en lactantes febriles menores de 90 días de vida [126][127][128] . Además, el riesgo de infecciones bacterianas invasivas secundarias a ITU, especialmente la bacteriemia, es mayor en estos pacientes 22,169,172 . El patrón oro para el diagnóstico de ITU es el crecimiento de un germen patógeno aislado en un cultivo de orina 71 .…”
Section: Using a Urine Dipstick To Identify A Positive Urine Culture unclassified
“…Hemos analizado una muestra grande, derivada de un estudio multicéntrico prospectivo desarrollado para elaborar un modelo predictivo de pacientes con sospecha de ITU y bajo riesgo de desarrollar una infección bacteriana invasiva (IBI) 172 . La muestra se dividió en 6 grupos, dependiendo de los resultados de la tira de orina (positivo o negativo) y del número de colonias aislado en el cultivo de orina.…”
Section: Importance Of Urine Dipstick In Evaluation Of Young Febrile unclassified
See 1 more Smart Citation